Communicating research on the economic valuation of coastal and marine ecosystem services. (January 2017) - Torres, Cati; Hanley, Nick
Abstract: Quantifying the monetary value of ecosystem services (ES) provided by coastal and marine resources can help policy makers assess the trade-offs and synergies inherent in ecosystem-based management of marine and coastal environments, thus increasing the social efficiency of decision-making processes. As shown by the valuation literature, the number of coastal and marine management settings where valuation researchers have attempted to make a contribution is rising fast. However, this rise in research activity has not been matched by the increase in the use of economic valuation (EV) in the actual management of coastal and marine resources. This raises an interesting question: is EV responding to the needs of policy makers? This paper provides a comprehensive overview of the knowledge base regarding the economic values for coastal and marine ecosystems. It then discusses how to improve the uptake of ES valuation research by focussing on two core issues which are thought to be essential for more effective communication with the policy community. Highlights: Understanding ecosystem service values can improve the efficiency of coastal and marine management. Ecosystem service values can also provide justification for conservation strategies. This paper asks whether the current valuation literature is fit for purpose in these regards. Recommendations are given to improve the contribution of valuation to management of coastal and marine ecosystems. The need for a closer integration of ecological science within valuation, and for more collaboration with political scientists is highlighted.